Called to Bless: Considering an Under-appreciated Aspect of "Doing Good" in 1 Peter 3:8–17. (August 2020) - Shaw, David M.
This article investigates the notion of mission as blessing in 1 Peter 3:8–17. Drawing on insights from both Social Identity Theory (SIT) and Narrative Transportation Theory (NTT), I consider how the use of Old Testament quotations and allusions are deployed in such a way as to subvert normal social identity processes by exhorting the recipients of 1 Peter to pursue a life oriented towards blessing one's opponents through the refusal to retaliate; the pursuit of holistic well-being; and the willingness to defend the hope of one's faith.